2017
DOI: 10.4081/jbr.2017.6578
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variation in total phenolic content in temperate brown algae

Abstract: Marine algae synthesize secondary metabolites such as polyphenols that function as defense and protection mechanisms. Among brown algae, Fucales and Dictyotales (Phaeophyceae) contain the highest levels of phenolic compounds, mainly phlorotannins, that play multiple roles. Four temperate brown algae (Cystoseira amentacea, Cystoseira compressa, Dictyopteris polypodioides and Padina pavonica) were studied for total phenolic contents. Total phenolic content was determined colorimetrically with the Folin-Ciocalteu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
13
1
Order By: Relevance
“…For Cystoseira sensu latu species inhabiting the infralittoral fringe and subjected to regular even if incomplete emersion of the thalli, which implies a direct exposure to solar radiation, a higher content of these compounds as compared with those of species inhabiting the continually submerged zone, is expected [105]. Instead, in C. amentacea and in C. compressa, inhabiting the infralittoral fringe, a lower value than D. polypodioides, inhabiting the continually submerged zone, was found [78]. Connan et al [79] reported a higher content of these compounds in brown algae growing at mid-tide level compared to that of species inhabiting either the low-tide level or the upper mid-littoral fringe.…”
Section: Of 19mentioning
confidence: 93%
See 3 more Smart Citations
“…For Cystoseira sensu latu species inhabiting the infralittoral fringe and subjected to regular even if incomplete emersion of the thalli, which implies a direct exposure to solar radiation, a higher content of these compounds as compared with those of species inhabiting the continually submerged zone, is expected [105]. Instead, in C. amentacea and in C. compressa, inhabiting the infralittoral fringe, a lower value than D. polypodioides, inhabiting the continually submerged zone, was found [78]. Connan et al [79] reported a higher content of these compounds in brown algae growing at mid-tide level compared to that of species inhabiting either the low-tide level or the upper mid-littoral fringe.…”
Section: Of 19mentioning
confidence: 93%
“…But only soluble phlorotannins change with environmental conditions, as those present in the cell wall seem to be relatively stable to environmental variations [39]. Phlorotannins vary within and among species, in relation to the growth rate, the thallus morphology [4,10,34,37,77,78] (Figure 3) or age; for instance, adult thalli present longer and more complex forms, more difficult to degrade or release, than young thalli [39]. The content of soluble and cell-wall-bound phlorotannins also change within a single plant and among individuals within the population.…”
Section: Ecological Role Of Phlorotanninsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within its broad geographical range Cystoseira barbata may show considerable morphological and chemical variation, related to environmental conditions. Some studies were conducted on this species using traditional morphometric measures (length, biomass, age) in the Black Sea area [5]. Many studies show great variability in the chemical composition of marine algae characteristics due to marine habitats, but also other factors such as water temperature, seasonal variations, marine pollutants, etc.…”
mentioning
confidence: 99%